Aplikasi Pengenalan Tata Cara Sholat Fardhu (Studi Kasus SDN 1 Pecoh Raya) - Annisa Lestari (Jurnal Media Celebes, 2024)
Elementary school students in grades 3, 4 and 5 at SDN 1 Pecoh Raya are still not optimal in receiving material on how to introduce fardhu prayers in class, because teachers who teach in the field of religion still use blackboard media. In terms of appearance (interface) it is not very popular among elementary school students, so it motivates students to understand the lessons on fardhu prayer procedures. The learning method for introducing fardhu prayers at SDN 1 Pecoh Raya currently uses direct practice which is appropriate and efficient, but the use of technology needs to be implemented because the younger generation is already very familiar with technology which is a problem in itself. This then causes some students to not be interested and ultimately unable to read the fardhu prayers. The main focus of this research is to create an application for introducing fardhu prayers so that students can receive the material provided from a technological perspective and with the aim of making it easier for religious teachers to present material on how to introduce fardhu prayers. After the application development was carried out, the application was then tested on teachers who would teach fardhu prayers. The validation results of the application that had been developed produced a validation score of 74% which was quite good, so the implementation of the fardhu prayer application was good enough to be implemented by teachers. in the classroom or outside of classroom learning.